Peran Masyarakat Terhadap Pendidikan Islam Perspektif Hadis - Hanna Salsabila; Fannia Masrur Aini; Mutia Rahmah; Dwi Meutia Hasni (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article examines the urgency of community involvement in Islamic education by referring to the principles contained in the hadiths of Prophet Muhammad SAW. In the Islamic perspective, education is not solely the responsibility of teachers or formal institutions, but a collective trust shared by all members of society. This study employs a qualitative method with a literature-based approach, utilizing primary sources in the form of authentic hadiths and relevant Islamic educational literature. The findings reveal that society plays a significant role in shaping morality, preserving religious values, and creating a social environment conducive to the learning process. Hadiths related to enjoining good and forbidding evil (amr ma’ruf nahi munkar), conveying even a single verse, and encouraging the pursuit of knowledge emphasize that every individual holds a strategic role in nurturing Islamic education.